Seroprevalence of Pertussis in The Gambia: Evidence for Continued Circulation of Bordetella pertussis Despite High Vaccination Rates. Issue 4 (April 2015) - Scott, Susana; van der Sande, Marianne; Faye-Joof, Tisbeh; Mendy, Maimuna; Sanneh, Bakary; Barry Jallow, Fatou; de Melker, Hester; van der Klis, Fiona; van Gageldonk, Pieter; Mooi, Frits; Kampmann, Beate
Abstract : Background: Bordetella pertussis can cause severe respiratory disease and death in children. In recent years, large outbreaks have occurred in high-income countries; however, little is known about pertussis incidence in sub-Saharan Africa. Methods: We evaluated antibody responses to pertussis toxin (Ptx) from individuals aged between 2 and 90 years in rural Gambia. IgG-Ptx was measured using luminex xMAP technology. IgG-Ptx geometric mean concentrations (GMC) and their 95% confidence intervals were calculated. The proportion seropositive (>20 EU/mL or ≥62.5 EU/mL) and GMCs were compared by age, sex, ethnic group, vaccination status, birth order and number of siblings per household using logistic and linear regression. Results: 76.3% had anti-Ptx levels <20 EU/mL, 17.5% had concentrations between 20 and 62.5 EU/mL, 4.4% had concentrations between 62.5 and 125 EU/mL and 1.8% had concentrations ≥125 EU/mL. The overall Ptx antibody GMC was 6.4 EU/mL (95% confidence interval: 5.8–6.9). Higher antibody concentrations were observed in older populations with evidence for an increase in infection risk with increasing age (1.9% yearly increase, 95% confidence interval: 1.3–2.5). No child under 6 years of age had GMC above 62.5 EU/mL but 29.5% had concentrations between 20 and 62.5 EU/mL. Conclusions: These data provide evidence that B. pertussis is being transmitted within this population despite high vaccination coverage. Re-infection may occur implying that immunity from childhood vaccination may not be lifelong. In the absence of data on actual clinical cases of pertussis, seroprevalence studies remain valuable tools to assess the transmission dynamics of B. pertussis . Abstract : Supplemental Digital Content is available in the text.